2021
DOI: 10.5771/1615-634x-2021-2-221
|View full text |Cite
|
Sign up to set email alerts
|

Learning by doing oder doing by learning? Die Wechselwirkung zwischen Online- Privatheitskompetenz und Datenschutzverhalten

Abstract: Die Nutzung von und die Kommunikation mit sozialen Medien basiert auf dem Austausch persönlicher Daten. Dabei können Privatheitsrisiken entstehen, vor denen man sich oft nur schwer schützen kann. Damit Menschen Online-Angebote selbstbestimmt nutzen können, ist ein gewisser Schutz ihrer Daten erforderlich. Immer häufiger wird die Online-Privatheitskompetenz als Voraussetzung dafür angesehen. Kritisch hinterfragt wird jedoch, ob Wissen über Online-Privatheit tatsächlich zu aktivem Datenschutz führt. Die Kausalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The results of this study revealed that more educated persons reported easier access to privacy information and had a higher privacy literacy which is consistent with previous studies (Büchi et al, 2021;Epstein & Quinn, 2020;Park, 2013;Schäwel et al, 2021). This finding suggests that people with a lower education might have difficulties in acquiring knowledge about privacy issues, are possibly embedded in networks in which such information is less prevalent, or lack such information as part of school, university, or professional training.…”
Section: Educationsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of this study revealed that more educated persons reported easier access to privacy information and had a higher privacy literacy which is consistent with previous studies (Büchi et al, 2021;Epstein & Quinn, 2020;Park, 2013;Schäwel et al, 2021). This finding suggests that people with a lower education might have difficulties in acquiring knowledge about privacy issues, are possibly embedded in networks in which such information is less prevalent, or lack such information as part of school, university, or professional training.…”
Section: Educationsupporting
confidence: 90%
“…In the present study, men reported easier access to privacy protection information in their daily routine and had a higher privacy literacy than women. These results are largely consistent with previous studies that found women to have a lower privacy literacy and (as a potential consequence) adopting less privacy protective measures online than men (Büchi et al, 2021;Matzner et al, 2016;Meier & Krämer, 2023;Schäwel et al, 2021). Consequently, women seem to be disadvantaged when compared to men when it comes to receiving information about how to protect one's privacy online which seems to be reflected in their level of actual privacy knowledge.…”
Section: Sexsupporting
confidence: 90%
See 2 more Smart Citations